2020
DOI: 10.2478/joim-2020-0038
|View full text |Cite
|
Sign up to set email alerts
|

How to Improve Communication within an Organization? The Relationship between Cultural Intelligence and Language Competence

Abstract: AbstractObjective: This article deals with the effective functioning of an organization in the international context. It focuses on the two key aspects of the communication in this respects: cultural intelligence (CQ), the capacity to operate successfully in the multicultural setting, and the quality of internal communication; it is investigated whether CQ (and its components: metacognitive, cognitive, motivational and behavioural) are rather related to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 59 publications
0
1
0
Order By: Relevance
“…Thomas (2006) remarked that the process of developing CQ may be rather slow due to the fact that time is a critical aspect in the acquisition of information. Additionally, Bücker and Korzilius (2015) demonstrated that the ability to comprehend and make sense of cultural cues, the motivation to adapt to the new environment and the capability to function correctly in the new environment (Jurásek & Potocký 2020) are critical components of the CQ development process.…”
Section: Cultural Intelligencementioning
confidence: 99%
“…Thomas (2006) remarked that the process of developing CQ may be rather slow due to the fact that time is a critical aspect in the acquisition of information. Additionally, Bücker and Korzilius (2015) demonstrated that the ability to comprehend and make sense of cultural cues, the motivation to adapt to the new environment and the capability to function correctly in the new environment (Jurásek & Potocký 2020) are critical components of the CQ development process.…”
Section: Cultural Intelligencementioning
confidence: 99%